Dealing with the contradiction of agency and control during dialogic teaching. (September 2016) - Rajala, Antti; Kumpulainen, Kristiina; Rainio, Anna Pauliina; Hilppö, Jaakko; Lipponen, Lasse
Abstract: This study investigated the contradiction between student agency and teacher control in classroom interactions during dialogic teaching. The study focused on interactional moments when the students opposed or questioned the instructional activity, because it was hypothesized that the agency-control contradiction (Rainio, 2008) becomes particularly evident in these moments. The video data were collected in a heterogeneous Finnish third-grade classroom and analyzed with interaction analysis. The results show how promoting student agency is a contradictory endeavor that requires balancing between the aspirations of dialogic teaching and institutional demands. The results showed that the students' criticism and questioning of instructional activity were targeted at the contents, procedures, and purpose of the instructional activity. We found inconsistency in the teacher's responses to the students' opposition according to the type of opposition. Providing space for negotiation created opportunities for achieving student agency. Conversely, the teacher also silenced students' opposition by enforcing his institutional authority or disregarding student opposition, resulting in interactions that suppressed student agency. This study adds to the understanding of what is at stake when students' agency is promoted in classroom interactions.